MODEL PEMBELAJARAN SISTEM BASIS DATA BERBASIS COMPUTER ASSISTED INSTRUCTION - Ruliah, Ruliah; Bahar, Bahar; Pratiwi, Andita Suci (Universitas Muhammadiyah Jakarta, 2020)
ABSTRACT The direct (face-to-face) learning approach that is centered on the teacher in Data Base System lectures causes the learning process to be passive. Students' understanding is not optimal in certain competencies so that the final average of students does not reach the predetermined competency standards. This paper presents a learning model for Computer Assisted Instruction (CAI) Database System with a combination of Tutorial and Drill and Practice models. The research uses the R & D (Research and Development) method with three main stages, namely conducting an initial study to find information about the learning model to be developed, developing a model based on the results of the problem study, and conducting field trials. The results of the pretest and posttest showed an increase in learning completeness by 72.41%, as evidenced by the significance test which experienced a significant increase. Keywords: Learning Model, Database System, Computer Assisted Instruction, Research and Development, Tutorial, Drill and PracticeABSTRAK Pendekatan pembelajaran langsung (tatap muka) yang berpusat pada pengajar dalam perkuliahan Sistem Basis Data menyebabkan proses belajar menjadi pasif. Pemahaman mahasiswa tidak maksimal pada bagian kompetensi tertentu sehingga rerata nilai akhir mahasiswa tidak mencapai standar kompetensi yang telah ditetapkan. Paper ini menyajikan model pembelajaran Sistem Basis Data berbantuan Komputer (Computer Assisted Instruction/ CAI) dengan kombinasi model Tutorial dan Drill and Practice. Penelitian menggunakan metode R & D (Research and Development) dengan Tiga tahapan utama, yaitu melakukan studi awal untuk mencari informasi mengenai model pembelajaran yang akan dikembangkan, mengembangkan model berdasarkan hasil kajian permasalahan, dan melakukan uji coba lapangan. Hasil uji pretest dan posttest menunjukkan adanya peningkatan ketuntasan belajar sebesar 72,41%, yang dibuktikan dengan uji signifikasi yang memperlihatkan adanya peningkatan yang signifikan. Kata Kunci: Model Pembelajaran, Sistem Basis Data, Computer Assisted Instruction, Research and Development, Tutorial, Drill and Practice